Long-Term Analysis of Respiratory-Related Complications Following Gastrostomy Placement with or without Fundoplication in Neurologically Impaired Children: A Retrospective Cohort Study - Elisa Zambaiti; Calogero Virgone; Silvia Bisoffi; Roberta Stefanizzi; Francesco Fascetti Leon; Piergiorgio Gamba (Children, 2021)
Gastrostomy placement is crucial in neurologically impaired (NI) children to ensure an adequate food intake and a safe route for drugs administration and to reduce the risk of primary aspiration. NI patents are more prone to gastroesophageal reflux. The association with fundoplication is deemed to reduce reflux-related respiratory complications. However, long-term benefits of this approach are not clear. We therefore aimed to compare long-term reflux-related respiratory complications of gastrostomy only (GO) to gastrostomy with fundoplication (GF). We retrospectively reviewed 145 consecutive NI children managed from 2008 to 2018. As long-term outcomes, we analyzed number and length of hospital admissions (Reflux-Related-Hospitalization, RRH) and emergency department accesses (Reflux-Related-Accesses, RRA) due to respiratory problems. Results were analyzed with appropriate statistical method. Median age at referral and at gastrostomy placement were 2.2 and 3.4 years (SD 5.6), respectively. Median follow-up was four years (range 1–12). Anti-reflux procedures were performed in 26/145 patients (18%); tracheotomy in 23/145 (16%). RRH following surgery showed lower number of admissions/year (0.32 vs. 1 for GO vs. GF, p < 0.005) and days hospitalization/year (3 vs. 13, p = 0.08) in GO compared to GF; RRA was similar (0.60 vs. 0.65, p = 0.43). Gastrostomy placement alone appeared not to be inferior to gastrostomy plus fundoplication with respect to long-term respiratory-related outcomes for NI children in our center.